Hydrological Implication of Bamboo And Mixed Garden In The upper Citarum Watershed - Chay Asdak (Faculty of Geography, Universitas Gadjah Mada, 2006)
The assessment of important factors affecting runoff and erosion was carried out by collecting runoff and soil loss from four runoff/erosion plots. The runoff/erosion plots were set up in sloping areas of about 40% slope in the upper area of Ciwidey sub-watershed (upper Citarum watershed), West Java. The plots (6 x 10 m) were established in the following four sets of conditions: bamboo plantation, mixed garden, small shrub, and agricultural field with different species and stand structures. After 20 rainfall events, a treatment in the form of removing undergrowth and litter were applied to bamboo and mixed garden plots. The result of this before and after treatment are the following: runoff from bamboo plantation was increased from 0.40 to 1.02 litre/m2 and erosion was increased from 1.47 to 11.65 gr/m2. While the runoff and erosion in mixed garden were increased from 0.36 to 1.65 litre/m2 and from 1.36 to 10.88 65 gr/m2, respectively. When this compared to the runoff and soil loss in the agricultural plot, the soil erosion is much higher, 50.5 gr/m2 (about 50 times higher). Stand/canopy structure appeared to be the important factors that determine the magnitude of soil erosion. While the role of these factors were less significant compared to rainfall in determining the magnitude of runoff.